Ocean Wave Power Plant With A Pendulum Drive System - Sofyan, Rakan Thariq (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2025)
This research explores the development and evaluation of a pendulum-driven wave energy conversion system designed to harness ocean wave motion for renewable energy production. The prototype system integrates a buoy, pendulum, gearbox, and generator to convert kinetic energy into electrical power. Testing revealed that the system achieved an average power output of 4.854 W, demonstrating sufficient performance despite inherent mechanical and electrical losses. The buoy design, optimized using Archimedes' principle, provided consistent energy capture, while the pendulum mechanism effectively transmitted this energy to the generator. Despite its advantages, the system exhibited limitations that require further exploration. Mechanical friction and resistive losses also reduced overall efficiency, indicating areas for improvement. This study underscores potential for the pendulum-based wave energy system as a promising approach to renewable energy production, leveraging the abundant and untapped resource of ocean waves.